A review of participatory epidemiology application in human health and nutrition and future directions - Mwiti Marangu, Victor; Robert Mburugu Kei; Dr. Dorothy Kagendo Kithinji (PhD.) (African Journal of Science, Technology and Social Sciences, 2024)
Participatory Epidemiology (PE) developed as a branch of veterinary epidemiology and has been widely used in infectious disease control and early warning in resource-limited settings. In the beginning, Participatory Epidemiology was focused on linking the researcher’s communication skills with participatory methods to enable the participation of livestock owners and herders in the identification and assessment of livestock diseases as well as in the development, monitoring, and evaluation of the disease control strategies. In this respect, the use of participatory techniques gradually developed into Participatory Epidemiology with increased recognition by epidemiologists who have developed several tools which are being adapted in human health and nutrition. Relative to veterinary uses and human nutrition, Participatory Epidemiology has not been used in public health in Kenya or for studies on important human diseases, such as Kala-azar. However, in the recent past there have been growing interests from epidemiologists to extend the testing and piloting of the Participatory Epidemiology approach in the arid and semi-arid settings of Kenya geared at empowering communities to identify and solve their health needs. Additionally, there is ongoing debate about the ability of epidemiology to give results that can be better applied in public health practice besides its ability to identify disease risk factors. Scientific research has recommended that participatory research be applied in epidemiology to bridge this descriptive gap and action. This review describes the implementation experiences and lessons learnt in the use of Participatory Epidemiology in understanding human diseases, both communicable and non-communicable as well as human nutrition, a key factor in health and wellness. The reviewed articles provide an understanding into the application of PE approaches which have been limited in pastoralist areas, where zoonotic diseases are prone. The article establishes that as opposed to more conventional methods, using Participatory Epidemiology can generate precise and scientifically credible information within a relatively short period. Data generated from Participatory Epidemiology can be sustainably used to effectively find solutions to the common community health problems based on local preferences for control options.